Discursos midiáticos e preconceito linguístico em disputa pelo dizer e silenciar - Viveiros, Danielle Christiane da Silva (2016)
Taking into consideration that speaking differently does not mean speaking “wrongly”, and that, many times, the linguistic heterogeneity is not acknowledge by the school and/or Portuguese language teachers, this work aims at contributing to the development of studies linked to the linguistic variables. The most common practices have been the prejudice and the intolerance in relation to the popular speaking forms, which are stigmatized and excluded as wrong forms. Although, in the last decade, the educational legislation has been making the guidelines that exclude the popular discourse form less rigid, we can see resistance to this idea, which is not only reinforced, but also embraced by the general press and by the means of communication. This work discusses the needs for adopting a political posturs in relation to this subject, which acknowledges that the point cannot be simplified to the adoption of a correct and true speaking form, whose arguments, in fact are in service of the maintenance of an authoritarian order, based on privileges and that excludes all those who do not practice the standardized form of the Portuguese language. Thus, the proposed aim for this work, as a result of bibliographical and documented research, is a linguistic reflection concerning the relation between: discourse, identity and alterity, as well as an analysis of the mediatic speeches produced since 2001 up to current times referring to the thematic, seeing these speeches as power and knowledge devices. The linguistic stigmatization remains as an impregnable beacon of inequality and finds support among the professors and students of Language, Linguistic and Pedagogy who intend to stablish a sort of monopoly over the national linguistic forms and manifestations. On the other hand, many researchers in the linguistic field have dedicated their research to the valorization of the popular speaking forms. Through a bibliographical study, the theoretical conceptions of the research are presented inside the functionalist and sociolinguistic perspective, basically aiming the communicative competence, a theory shown in: Bakhtin (1979 and 1992), Labov (2008), Neves (1990, 1997, 2003, 2006 and 2010), Bagno (2003, 2009, 2010 and 2011), Leite (2005 and 2008), Possenti (2005 and 2012), Gnerre (2009); Bortoni-Ricardo (2004 and 2005) among others; in addition to the scholars linked to the Human Sciences who deals with the study of the discourse as language is a social behavior and manifestation of the fight for power– Foucault (1995, 1996, 1999 and 2009), of Philosophy and Bourdieu (1975, 1989, 1998, 2001 e 2008), of Sociology and Habermas (1987). This way, the analysis focus in the real usages of the language and pursues the explanation of these processes activated in various textual genres (journalistic, political debates, cartoons, charges, paintings and pictures) to exemplify the analysis and the theoretical apparatus as well. Concerning the teaching of the Portuguese language, speeches and documents related to the new forms to teach grammar are not enough if these are not incorporated to the pedagogical practice. The grammar teaching should be brought close to the reality of the usage and dynamism of the Portuguese language; however, we cannot forget that the norms in the grammar compendium have a space, which, necessarily, should be respected and taught. Furthermore, when we praise the standard practice of the language and raise the view of “right” and “wrong”, without considering the other forms of the language, the mediatic speeches help to spread the linguistic prejudice. The prejudiced metadiscourse also report other prejudices of social, racial, political, religious order among others and the teachers and school administrators need to know how to acknowledge them within the school scope in order to, on one side, act in a critical and conscious way in the face of the occurrences of these phenomena and to, on the other side, help to avoid its manifestation. Such attitude is part of the whole development of citizenship, because it is also an indicative of respecting the differences of the other.